The Fallacy of the Bolted Horse: Changing Our Thinking About Mature-Age Aboriginal and Torres Strait Islander University Students - Plater, Suzanne; Mooney-Somers, Julie; Lander, Jo (The Australian Journal of Indigenous Education, 2015)
The aim of this article is to critically review and analyse the public representations of mature-age university students in developed and some developing nations and how they compare to the public representations of mature-age Aboriginal and Torres Strait Islander university students in Australia (‘students’ also refers to graduates unless the context requires specificity). Relevant texts were identified by reviewing education-related academic and policy literature, media opinion and reportage pieces, conference proceedings, and private sector and higher education reviews, reports and submissions. What this review reveals is striking: very few commentators are publicly and unambiguously encouraging, supporting and celebrating mature-age Aboriginal and Torres Strait Islander university students. This strongly contrasts with the discussions around mature-age university students in general, where continuous or lifelong learning is acclaimed and endorsed, particularly as our populations grow older and remain healthier and there are relatively lower numbers of working-age people. While scholars, social commentators, bureaucrats and politicians enthusiastically highlight the intrinsic and extrinsic value of the mature-age student's social and economic contributions, the overarching narrative of the mature-age Aboriginal and Torres Strait Islander student is one of ‘the horse has bolted’, meaning that it is too late for this cohort and therefore society to benefit from their university education. In this article we examine these conflicting positions, investigate why this dichotomy exists, present an alternative view for consideration, and make recommendations for further research into this area.